Click-based functionalization of a 2′-O-propargyl-modified branched DNA nanostructure. Issue 11 (2nd March 2017) - Valsangkar, Vibhav; Chandrasekaran, Arun Richard; Wang, Rui; Haruehanroengra, Phensinee; Levchenko, Oksana; Halvorsen, Ken; Sheng, Jia
Abstract : We report a click-based strategy to incorporate a metal chelating (bipyridine) ligand and a fluorescent tag (FAM) into a three-point-star DNA tile containing 2′- O -propargyl groups. Abstract : DNA has emerged as a versatile building block for programmable self-assembly. DNA-based nanostructures have been widely applied in biosensing, bioimaging, drug delivery, molecular computation and macromolecular scaffolding. A variety of strategies have been developed to functionalize these nanostructures. In this study, we report a facile click-based strategy to incorporate a metal chelating ligand and a fluorescent tag into a three-point-star DNA tile containing 2′- O -propargyl groups. Such a strategy opens up the possibility of functionalizing pre-assembled DNA strands to construct platforms for metal or drug delivery.